2016
DOI: 10.1182/blood-2015-09-668145
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies from donor B cells perpetuate cutaneous chronic graft-versus-host disease in mice

Abstract: • Antibodies produced by donor B cells are required for thymic and lymphoid damage in mice with chronic GVHD.• Antibody-producing donor B cells associate with infiltration of Th17 cells in the skin and perpetuation of cutaneous chronic GVHD in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 52 publications
(64 reference statements)
5
89
0
1
Order By: Relevance
“…This result could be attributed to XBP-1-dependent defects in dendritic cell-derived type I IFN signaling, which regulates T-cell survival, 10,66 from chemotactic signals such as CXCL16 produced by nonhematopoietic cells, also regulated by XBP-1, 67 or from antibody-mediated cutaneous infiltration of pathogenic Th17 cells. 29,65 In spleens, frequency of total granulocytes was significantly reduced after B-I09 administration in the B10.D2 to BALB/c model (data not shown), in agreement with previous reports indicating that XBP-1 is critically involved in the differentiation and recruitment of granulocyte subsets into tissues leading to inflammatory fibrosis, 11,68,69 and that these subsets are involved in cGVHD. 70,71 Current leading therapies for cGVHD directly target B cells or T cells, 31,60 whereas the current study and previous literature suggest that inhibition of the IRE-1a/ XBP-1 pathway via B-I09 could directly impact other cell subsets involved in cGVHD development in addition to B cells and T cells, 65 such as dendritic cells, 10 granulocytes, 11 and even nonhematopoietic cells.…”
Section: Org Fromsupporting
confidence: 80%
See 3 more Smart Citations
“…This result could be attributed to XBP-1-dependent defects in dendritic cell-derived type I IFN signaling, which regulates T-cell survival, 10,66 from chemotactic signals such as CXCL16 produced by nonhematopoietic cells, also regulated by XBP-1, 67 or from antibody-mediated cutaneous infiltration of pathogenic Th17 cells. 29,65 In spleens, frequency of total granulocytes was significantly reduced after B-I09 administration in the B10.D2 to BALB/c model (data not shown), in agreement with previous reports indicating that XBP-1 is critically involved in the differentiation and recruitment of granulocyte subsets into tissues leading to inflammatory fibrosis, 11,68,69 and that these subsets are involved in cGVHD. 70,71 Current leading therapies for cGVHD directly target B cells or T cells, 31,60 whereas the current study and previous literature suggest that inhibition of the IRE-1a/ XBP-1 pathway via B-I09 could directly impact other cell subsets involved in cGVHD development in addition to B cells and T cells, 65 such as dendritic cells, 10 granulocytes, 11 and even nonhematopoietic cells.…”
Section: Org Fromsupporting
confidence: 80%
“…56 In our study, XBP-1-deficient B cells produced significantly less IL-12p40 and IL-4/5 cytokines after LPS and IL-4 stimulation, suggesting that XBP-1 regulates both type 1 and 2 effector B-cell differentiation. Although some of our B-cell data can be connected to an intrinsic defect of BCR signaling and S1P1 from XBP-1 deficiency, 17 we have demonstrated that BM+Sp+B-I09 2.5 29 Here, XBP-1-deficient B cells secreted less antibodies in response to both in vitro and in vivo stimuli, and both in vitro and in vivo treatment with B-I09 phenocopied this effect. XBP-1 KO B cells also engaged in less class-switch recombination after allo-BMT compared with XBP-1 WT B cells, where higher retention of surface IgM was consistent with reduced levels of serum anti-dsDNA IgG, consistent with a previous report that XBP-1 KO B cells express less activation-induced cytidine deaminase.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…30 A recent study showed that antibodies from donor B cells perpetuate cutaneous sclerotic GVHD in mice. 31 Functional activation of T cells depends on surface expression of TCR-CD3 complexes. CD247 encodes the TCR z (CD3z) subunit and plays a crucial role in coupling antigen recognition to several intracellular signal-transduction pathways.…”
Section: Discussionmentioning
confidence: 99%